Moleccular analysis of evolutionary changes in populations of Ophiostma novo-ulmi - Brasier, C.=700 1 Buck, K.; Paoletti, M.; Crawfoerd, L.; Kirk, S.
(Es, En)
ilus., 30 ref.
Keywords: OPHIOSTOMA; CLONES; HIBRIDACION; VIRUS; ESPAÑA; GRAFIOSIS